A study on the optimal path of methane emissions reductions in a municipal solid waste landfill treatment based on the IPCC-SD model. (10th June 2019) - Qu, Sijia; Guan, Dongjie; Ma, Zhanyun; Yi, Xiaotao
Abstract: This paper provides a comprehensive analysis of the methane emission reduction technology and reduction potentials from MSW. Based on calculate the methane emissions at multiple scales to analyse the dynamic change in the spatial distribution from 2001 to 2015, and this study simulates the trends of methane emissions in Chinese Cities from 2015 to 2050 by coupling the IPCC method with the SD model. The results indicate that the methane emissions in each region had been growing steadily from 2001 to 2015. After the adoption of methane emission reduction technology, the methane emissions have decreasing trend, and the peak value will show up mainly from 2026 to 2029. The methane emissions of each province under different single and comprehensive technical scenarios less are 0–60 Gg and 110–150 Gg than that in the standard scenario. The CO scenario has the largest emission reduction in single emission reduction technology scenario, and can reach 600.11 Gg in 2050; The F stages FER scenario has the largest emission reduction in comprehensive emission reduction technology scenario, and can reach 2020.9 Gg in 2050. However, Comprehensive consideration the emission reduction potential and emission reduction cost, the SER at BE technology can be regarded as the optimal emission reduction technology. The technology scenario for emission reduction and data collected in this study can help reduce methane emission from MSW landfill, which supports decision-making regarding the cyclic utilization of MSW and mitigation the impact of waste on climate change. Highlights: The IPCC method and SD model are combined is presented for calculating methane emission of MSW. The variation trend of methane emission in Chinese city and the peak point of methane emission in China are shown. Ten technology scenarios are considered for methane emission reduction of MSW in China. The optimal emission reduction path is comprehensive evaluated.